1973
DOI: 10.1002/j.1537-2197.1973.tb07595.x
|View full text |Cite
|
Sign up to set email alerts
|

Orchid Mycorrhiza: Vitamin Production and Requirements by the Symbionts

Abstract: A Rhizoctonia species isolated from Cymbidium has been cultured successfully on a defined medium consisting of minerals, sugar, thiamine, and folic acid. Thiamine can be replaced by its thiazole component, which is probably produced by germinating orchids. The fungus apparently produces the pyrimidine moiety of thiamine, a compound which may enhance growth of certain orchid seedlings. Niacin is also provided by the fungus. Para‐aminobenzoic acid, a constituent of folic acid, produced and released by orchid see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…As a result of the conversation, he mailed the notebook to J.A. who interpreted the data and wrote a paper based on them (Hijner and Arditti 1973). Went refused to be listed as a coauthor due to his long-standing policy not to add his name to papers by his students.…”
Section: Who Are the Pioneers?mentioning
confidence: 99%
“…As a result of the conversation, he mailed the notebook to J.A. who interpreted the data and wrote a paper based on them (Hijner and Arditti 1973). Went refused to be listed as a coauthor due to his long-standing policy not to add his name to papers by his students.…”
Section: Who Are the Pioneers?mentioning
confidence: 99%
“…was heterotrophic for the thiazole moiety of the thiamin molecule and p-aminobenzoic acid or other substances related to folic acid (Hijner and Arditti, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…At least one strain of T. calospora requires yeast extract for growth (Hadley, 1970), whereas R. repens M 32 did not exhibit such a need. However nutritional requirements of orchid fungi should not be taken to indicate systematic relationships since they may vary from strain to strain (Hijner & Arditti, 1973;Mariat, 1948Mariat, , 1951Stephen & Fung, 1971;Vermeulen, 1947).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the nutritional requirements of selected orchid fungi have been determined (Burgeff, 1959;Downie, 1949;Hadley, 1969;Hijner & Arditti, 1973;Hollander, 1932;Mariat, 1951;Stephen & Fung, 1971). In several instances it has been shown that the fungi require vitamins or their precursors, amino acids or combinations of these.…”
Section: Introductionmentioning
confidence: 99%